Quantitative evaluation of the sacroiliac joint fixation in stress reduction on both sacroiliac joint cartilage and ligaments: A finite element analysis. (May 2021) - Venayre, Brice; Koyama, Yuichiro; Kurosawa, Daisuke; Hammer, Niels; Lingslebe, Uwe; Murakami, Eiichi; Ozawa, Hiroshi; Ohashi, Toshiro
Abstract: Background: The sacroiliac joint fixation is the last resort for patients with prolonged and severe joint pain. Although the clinical results of anterior fixations are conclusive, there exist several inevitable drawbacks with the surgical method such as the difficulty performing the surgery due to the presence of many organs. The posterior fixation technique has thus been developed to overcome those inconveniences. This study aims to assess in silico the mechanical environment following posterior and anterior fixations, focusing on stresses in both the sacroiliac cartilage and dorsal ligamentous part, as well as loads experienced by the pelvic ligaments. Methods: Sacroiliac joint cartilage, dorsal ligamentous part stresses and pelvic ligaments loads were evaluated with three types of fixation models. A vertical load of 600 N was applied, equally distributed via both acetabula when standing and sitting. Findings: Results show that the anterior sacroiliac joint fixation reduced von Mises stresses in the cartilage and dorsal ligamentous part and decreased ligaments loads more extensively than the posterior fixation when compared to the untreated model as a reference. However, the posterior fixation still remains the desirable and preferential treatment. Interpretation: The anterior sacroiliac joint fixation showed better performances compared to the posterior one; however, the lower invasive aspect of the latter is a fundamental clinical advantage which also has the possibility to be improved by considering various screws and cages configurations. This study provides a beneficial suggestion to improve the current fixation technique. Highlights: Screws and cages improve the biomechanical stability of sacroiliac joints. Sacroiliac joint anterior fixations show better performances than posterior ones. An implant's direction largely influences stress distributions. Varying implant's directions alter the pelvic ligaments total loading.